Boosting Mass Transit through Entrepreneurship : Going beyond Subsidies to Reduce the Public Transport Funding Gap - Pulido, Daniel; Portabales, Irene (World Bank Group, Washington, DC, 2015)
Most of the world’s urban mass transit systems cannot cover operating costs, let alone capital expenses, through farebox revenues. On average, 25 percent of metro operating expenditures are not funded by farebox income. With limited public subsidies, as well as obstacles to raising fares and political sensitivities to road user taxes, metro systems have been increasingly pursuing income from commercial activities connected with their operations. Metro systems earn commercial income, such as from advertising, naming rights, and especially real estate activities, are making inroads in their operating deficits. Commercial revenue in some systems is nearing 20 percent of fare revenue. Although reforms of transit financing structures remain high on the policy agenda, a review of ancillary income streams of metro systems around the world shows that a more entrepreneurial approach to tapping their commercial potential can help them narrow their funding gap.